Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5303/pkas.2015.30.2.491
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Gas Properties Under Icm Pressure in the Cluster Environment

Abstract: We present 12CO (2−1) data for four spiral galaxies (NGC 4330, NGC 4402, NGC 4522, NGC 4569) in the Virgo cluster that are undergoing different ram pressure stages. The goal is to probe the detailed molecular gas properties under strong intra-cluster medium (ICM) pressure using high-resolution millimeter data taken with the Submillimeter Array (SMA). Combining this with Institut de RadioAstronomie Millimétrique (IRAM) data, we also study spatially resolved temperature and density distributions of the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hence, using the Submillimeter Array (SMA) 1 , we have taken high-resolution 12CO (2−1) imaging data of a subsample of Virgo galaxies that have lost atomic gas significantly by ICM pressure. Some preliminary results are published in Lee & Chung (2015), and in this work, we present more complete analysis on both morphology and kinematics of three Virgo galaxies based on the SMA data.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, using the Submillimeter Array (SMA) 1 , we have taken high-resolution 12CO (2−1) imaging data of a subsample of Virgo galaxies that have lost atomic gas significantly by ICM pressure. Some preliminary results are published in Lee & Chung (2015), and in this work, we present more complete analysis on both morphology and kinematics of three Virgo galaxies based on the SMA data.…”
Section: Introductionmentioning
confidence: 99%
“…The one-sided HI filaments are not always traced by close companions, such as NGC 4654 (Phookun & Mundy 1995), NGC 4330, NGC 4402, NGC 4522 and NGC 4569 in Virgo cluster (Chung et al 2009;Lee & Chung 2015). These galaxies appear to have head-tail shapes, with a compressed edge on one side and a long tail on the other side.…”
Section: Physical Properties Of the Galaxymentioning
confidence: 99%
“…A typical ram-pressure stripped HI morphology shows a headtail shape (Gavazzi et al 1995;van Gorkom et al 2003;Kenney et al 2004;Lee & Chung 2015). By mapping the HI gas distribution of galaxies in Virgo cluster, Chung et al (2009) found a remarkable number of galaxies with long, one-sided HI tails pointing away from M87, which were proposed to be the effect of ram-pressure stripping, in the sense that these galaxies are falling into the Virgo core for the first time.…”
mentioning
confidence: 99%